Politics and Law Implementing the New Normal Pandemic Covid -19 in Society di Bandar Lampung City - Kusuma Arcaropeboka, Rj Agung; Sanusi, Afriadi Bin (Pandecta Research Law Journal, 2024)
The Covid-19 pandemic and the spread of its new variants are still ongoing, causing many casualties worldwide, including in Indonesia, and impacting all sectors of life. The government has taken measures such as issuing regulations to combat the coronavirus pandemic, along with derivative regulations at the regional level, and launching a mass vaccination program to protect citizens from contracting this outbreak. Based on the above description, the objectives of this research are to identify and analyze 1) the alignment of the implementation of the new normal policy with the objectives of the state in the context of the Covid-19 pandemic; 2) the implementation and impact of the new normal in promoting a healthy lifestyle in Bandar Lampung City; and 3) the main factors that hinder the implementation of the new normal concept in Bandar Lampung City. This research is a normative and empirical legal study based on socio-legal aspects. The social settings are the local government offices of Bandar Lampung City, and the object of this research is the role of the local government of Bandar Lampung City in protecting the community, particularly in preventing the spread of the Covid-19 outbreak. Data were obtained through document studies and interviews, then validated through source analysis and research methodology. Based on the research, it was found that the condition of the Covid-19 outbreak with its new variants is currently fluctuating, tending to gradually decrease. However, the government remains vigilant regarding the fluctuating spread of the Covid-19 outbreak. Advisories for mask usage, vaccination, and health protocols are continuously disseminated to the public. Moreover, the participation of community leaders along with task forces in their respective areas is very useful in prevention and guidance to support the implementation of Covid-19 management. Thus, the new normal life can be applied by using health protocols in each environment.